Fosaprepitant as combination therapy to prevent chemotherapy-induced vomiting in children: a meta-analysis - Shi, Yanshuo; Yue, Yuanyuan; Zhang, Yue; Pang, Guoxun (Frontiers in Pharmacology, 2025)
ObjectiveTo systematically evaluate the clinical efficacy and safety of fosaprepitant combined with 5-hydroxytryptamine 3 receptor antagonists (5-HT3RA) (with or without dexamethasone) on the chemotherapy-induced vomiting in pediatric cancer patients.MethodsPubMed, Embase, Cochrane Library, China Journal full-text database (CNKI), Wanfang data knowledge service platform (Wanfang) and VIP Chinese sci-tech Journal full-text database (VIP) were searched by computer (retrieval time from database establishment to Apr. 2024), randomized controlled trials (RCTs) and cohort studies about fosaprepitant and 5-HT3RA with or without dexamethasone (observation group) versus 5-HT3RA, with or without dexamethasone, as the control group for chemotherapy-induced vomiting were collected, after data extraction and quality evaluation, meta-analysis was carried out by Rev Man 5.3 software.ResultsA total of 731 patients were included in 7 trials. Meta-analysis results showed that the complete response (CCR, no vomiting/rescue medication) rates were higher in the observation group compared to that in the control group during the acute [the relative risk: RR = 1.64, 95% confidence interval: 95%CI = 1.35–1.99, P < 0.00001], delayed vomiting [RR = 2.05, 95%CI = 1.32–3.17, P = 0.001] and overall phases [RR = 2.08, 95%CI = 1.69–2.57, P < 0.00001], with statistical significance (P < 0.05). The subgroup analysis of salvage treatment proportion revealed that the need for rescue medication was higher for patients in the control than fosaprepitan regimens [RR = 0.20, 95%CI = 0.08–0.54, P = 0.001] There was no difference in the incidence of adverse drug reaction between two groups [RR = 0.95, 95%CI = 0.75–1.19, P = 0.66].ConclusionFosaprepitant in combination with 5-HT3RA (with or without dexamethasone) has the same safety and more effective in preventing chemotherapy-induced vomiting than 5-HT3RA with or without dexamethasone.